Dampak Sistem Informasi Manajemen Terhadap Produktivitas Dan Kinerja Pegawai Pada Organisasi Pemerintah Daerah (Studi Pada Pemerintah Daerah Kabupaten Labuhanbatu Tahun 2024) - Muhammad Habibi Siregar; Muhammad Irwan Padli Nasution (CV. SINAR HOWUHOWU, 2026)
The purpose of this study is to look at how employee performance and productivity are affected by the installation of the Management Information System (MIS) by the Labuhanbatu Regency Government. As a tactic for bureaucratic modernization, it is anticipated that the use of MIS in the public sector will enhance the efficacy, efficiency, and caliber of public services. One hundred State Civil Apparatus (ASN) from different local government work units participated in this quantitative survey study approach. Multiple linear regression analysis was used to look at how the independent variables affected the dependent variable. The results of the study show that staff productivity is positively and significantly impacted by the adoption of a Management Information System (MIS), with a regression coefficient of 0.612 and a significance value (p) of 0.000.Additionally, the Management Information System significantly and favorably affects employee performance, with a regression coefficient of 0.487 and a p value of 0.000. These findings show that when a MIS is successfully implemented, personnel productivity and performance in local government settings increase.